2012
DOI: 10.1586/eri.12.37
|View full text |Cite
|
Sign up to set email alerts
|

Role of GB virus C in modulating HIV disease

Abstract: GB virus C (GBV-C) is a member of the Flaviviridae family and the most closely related human virus to HCV. However, GBV-C does not replicate in hepatocytes, but rather in lymphocytes. GBV-C has a worldwide distribution and is transmitted sexually, parenterally and through mother-to-child transmission. Thus, co-infection with HCV and HIV is common. Until now, no human disease has been associated with GBV-C infection. However, there are several reports of a beneficial effect of GBV-C on HIV disease progression i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
36
0
1

Year Published

2016
2016
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 32 publications
(39 citation statements)
references
References 147 publications
2
36
0
1
Order By: Relevance
“…HIV-1/GBV-C co-infected individuals display higher CD4+ T cell counts, lower mortality rate, slower progression to AIDS and survive three times longer than HIV-1 monoinfected individuals [3,26,27]. Researchers debate whether the beneficial effects of coinfection of GBV-C in HIV-1-infected individuals are due to GBV-C viremia, or rather the presence of GBV-C anti-E2 antibodies or GBV-C NS5 antigen [3,5,27]. Previously, we demonstrated that the observed beneficial effects are due to modulation of the miRNAs in the coinfected host cells influencing the intracellular defense system [3,27].…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…HIV-1/GBV-C co-infected individuals display higher CD4+ T cell counts, lower mortality rate, slower progression to AIDS and survive three times longer than HIV-1 monoinfected individuals [3,26,27]. Researchers debate whether the beneficial effects of coinfection of GBV-C in HIV-1-infected individuals are due to GBV-C viremia, or rather the presence of GBV-C anti-E2 antibodies or GBV-C NS5 antigen [3,5,27]. Previously, we demonstrated that the observed beneficial effects are due to modulation of the miRNAs in the coinfected host cells influencing the intracellular defense system [3,27].…”
Section: Discussionmentioning
confidence: 99%
“…miRNAs present a powerful forward genetics approach to dissect virus-host cell interactions [4][5][6]. By using human genome-wide miRNA multi-genome alignments we identified a total of 76 human miRNAs that can potentially silence HIV-1 at different stages of the viral life cycle.…”
Section: Mirnas Silence Numerous Viruses In Susceptiblementioning
confidence: 99%
See 3 more Smart Citations